Third-hand Smoke: Impact on Hemostasis and Thrombogenesis. Issue 2 (August 2015) - Karim, Zubair A.; Alshbool, Fatima Z.; Vemana, Hari Priya; Adhami, Neema; Dhall, Sandeep; Espinosa, Enma V. P.; Martins-Green, Manuela; Khasawneh, Fadi T.
Abstract : Abstract: Cigarette smoking is a major risk factor for acute coronary thrombosis. In fact, both active/first-hand smoke and passive/second-hand smoke exposure are known to increase the risk of coronary thrombosis. Although recently a new risk has been identified and termed third-hand smoke (THS), which is the residual tobacco smoke contaminant that remains after a cigarette is extinguished, it remains to be determined whether it can also enhance the risk of thrombogenesis, much like first-hand smoke and second-hand smoke. Therefore, the present studies investigated the impact of THS exposure in the context of platelet biology and related disease states. It was found that THS-exposed mice exhibited an enhanced platelet aggregation and secretion responses as well as enhanced integrin GPIIb-IIIa activation. Furthermore, it was found that THS exposure shortens the tail bleeding time and the occlusion time in a model of thrombosis. Thus, our data demonstrate for the first time (at least in mice) that THS exposure increases the risk of thrombosis-based disease states, which is attributed, at least in part, to their hyperactive platelets.